Application of Xylenol Orange as an Adsorption Indicator in the Precipitimetric Assaying of Some Anions - Kumar, Rajiv; Chaturvedi, G.K. (Asian Journal of Chemistry, 2010)
Xylenol orange has been successfully employed as an adsorption indicator in the semimicro estimation of fluoride, metaborate, oxalate, sulphate and phosphate ions against lead(lI) ions in the acetate buffer (pH = 4.99), hexamine buffer (pH = 6.2) and pyridine buffer (pH=6.00) media. The indicator exhibited a sharp colour change from purple to bluish violet on the surface of the precipitate at the end point.